Legal Analysis Of The Legal Status Of Authentic Deeds Forged By Notaries - Putro, Fadli Asri; Riewanto, Agus; Lukitasari, Diana (Siber International Journal of Advanced Law (SIJAL), 2025)
Thesis entitled Juridical Analysis of the Legal Status of Authentic Deed forged by Notary examines the case of forgery of power of sale deed by Notary Madiyana Herawati based on Semarang District Court Decision Number 773/Pid.B/2021/PN Smg. The background of the problem is the need for legal certainty for victims of forged authentic deeds that harm land ownership rights. The research aims to evaluate the state's guarantee of certificate property rights and the judge's consideration in the verdict. Using the normative juridical method by referring to Law No. 2 of 2014, UUPA, and the Civil Code, the research found that the fake deed is null and void because it does not fulfil the requirements of an agreement (Article 1320 of the Civil Code). However, the judge's decision has not provided an effective remedy for the victim, Suratinah, regarding the transferred land ownership rights. The research concludes that there is a need for a judge's decision instructing the cancellation of legally defective certificates through the BPN and the provision of restitution to ensure justice. These results contribute to the understanding of the legal status of forged deeds and provide practical input for notaries, judges and the BPN in preventing and dealing with the forgery of authentic deeds.